An investigation of geometrically induced swirl applied to lean phase pneumatic flows - Fokeer, Smeeta (2006)
This thesis provides unique insights into the application of a geometrically induced swirl by a three-lobed helix pipe on a lean phase of particulate suspension in air along a horizontal pipe section. A series of experimental and computational studies were applied to three flow conditions employing high speed photography, Particle Image Velocimetry (PIV) and Laser Doppler Anemometry (LDA), as well as Computational Fluid Dynamics (CFD) techniques. The CFD simulation predictions were validated both qualitatively and quantitatively against the experimental data and were then used to obtain further insights into the characteristics of the flow behaviour.